An Experimental Study to Demonstrate the Extents of Reversible Changes after Withdrawal of Allethrin Based Mosquito Coil Smoke Exposure along with the Possible Protective Role of Vitamin C on Induced Testicular Changes in Male Wistar Albino Rats - Singh, Dr. Heena; Kumar, Dr. Navneet; Singh, Dr. Raghvendra; Manik, Dr. Punita; Rani, Dr. Archana; Diwan, Dr. Rakesh Kumar (International Journal of Innovative Research in Medical Science, 2016)
This study was an attempt to delineate the effect of allethrin based mosquito coil exposure on male fertility of wistar albino rats. This also includes two months of discontinuation of exposure to know whether there is any reversibility of changes. We also studied the role of an antioxidant (Vitamin C) in ameliorating the effect caused by the coil.The animals in our study were randomized into four groups: group I served as control rats; group II, III and IV received mosquito coil smoke 8 hours a day, 7 days a week for 12 week. Group IV rats co-administered oral supplementation of Vit. C (20 mg/kg body weight) once in a day for the same time period while group III animals were further kept for 8 weeks without any exposure to demonstrate withdrawal effect. Mean testicular weight was maximum in Group IV(1.83±0.30 gm) followed by group I(1.56±0.19gms), group III(1.22±0.42 gms) and group II(0.64±0.09 gm). Mean sperm count ranged from 83.75±9.61 units in Group II to 100.0±16.68 units in Group III, 130.7±14.14 units in Group IV and 157.7±7.92 units (Group I). Mean % abnormal sperm morphology was maximum in Group II (36.95±7.87%) followed by Group III (30.66±9.59%), Group IV (11.97±2.74%) and Group I (5.37±1.28%). Statistically, this difference was significant (p<0.001). This study demonstrates different types of abnormal sperm morphology. This study has its own merit that it also depicts the possible improvement after discontinuation of exposure and vitamin C supplementation.